Interfacial Sites in Ag Supported Layered Double Oxide for Dehydrogenation Coupling of Ethanol to n‐Butanol. Issue 11 (26th January 2021) - Zhang, Jian; Shi, Kai; Zhu, Yanru; An, Zhe; Wang, Wanning; Ma, Xiaodan; Shu, Xin; Song, Hongyan; Xiang, Xu; He, Jing
Abstract: Upgrading of ethanol to n ‐butanol through dehydrogenation coupling has received increasing attention due to the wide application of n ‐butanol. But the enhancement of ethanol dehydrogenation and followed coupling to produce high selectivity to n ‐butanol is still highly desired. Our previous work has reported an acid‐base‐Ag synergistic catalysis, with Ag particles supported on Mg and Al‐containing layered double oxides (Ag/MgAl‐LDO). Here, Ag‐LDO interfaces have been manipulated for dehydrogenation coupling of ethanol to n ‐butanol by tailoring the size of Ag particles and the interactions between Ag and LDO. It has been revealed that increasing the population of surface Ag sites at Ag‐LDO interfaces promotes not only the dehydrogenation of ethanol to acetaldehyde but also the subsequent aldol condensation of generated acetaldehyde. A selectivity of up to 76 % to n ‐butanol with an ethanol conversion of 44 % has been achieved on Ag/LDO with abundant interfacial Ag sites, much superior to the state‐of‐the‐art catalysts. Abstract : Synergistic Catalysis : Upgrading of ethanol to n ‐butanol through dehydrogenation coupling provides a sustainable way for n ‐butanol production. But high selectivity to n ‐butanol is still desirable. In this work, Ag‐LDO interfaces have been manipulated for dehydrogenation coupling of ethanol to n‐butanol by tailoring the size of Ag particles and the interactions between Ag and LDO. Increasing the population of interfacial Ag sites promotes not only the dehydrogenation of ethanol to acetaldehyde but also the subsequent aldol condensation. A selectivity of up to 76 % to n ‐butanol with an ethanol conversion of 44 % has been achieved on Ag/LDO with abundant interfacial Ag sites.